First record of the genus Acropimpla Townes, 1960 (Hymenoptera: Ichneumonidae: Pimplinae) from Thailand, with descriptions of three new species - Varga, Oleksandr; Reshchikov, Alexey (Zootaxa, 2015)
Nine species of Acropimpla Townes, 1960 are recorded from Thailand with three species described as new: A. leoni sp.n., A. natae sp.n., A. patellalutea sp.n. Six species, A. aspera Gupta & Tikar, 1976, A. hapaliae (Rao, 1953), A. leucostoma (Cameron, 1907), A. nakula Gupta & Tikar, 1976, A. taishunensis Liu, He & Chen, 2010, and A. uchidai (Cushman, 1933) are recorded from Thailand for the first time. A key to the females of Acropimpla species in South East Asia is also provided.